Experimental Study on Compressive and Tensile Strength of Plain Concrete With Polyethylene Terephthalate (PET) Powder - Karna, Neha Kumari; Shrestha, Nitesh (Everest Advances in Science and Technology, 2025)
This study examines the compressive strength and split tensile strength of concrete with polyethylene terephthalate (PET) powder as a partial replacement for sand in varying proportions. PET is a polymer commonly used in the food packaging industry, including cold drink and water bottles, and is considered a waste material. In this research, PET powder derived from recycled plastic bottles collected by a recycling plant in Itahari, Nepal, was utilized. Concrete specimens incorporating PET powder at proportions of 3.8%, 4.0%, and 4.2% by weight of sand were cast and tested for strength development at 7, 21, and 28 days. Cube and cylinder specimens were prepared using a water-to-cement ratio of 0.5. Results indicated that the inclusion of PET powder enhanced early-age compressive strength. At 7 days, concrete mixes with 3.8%, 4.0%, and 4.2% PET exhibited compressive strength increases of 26.44%, 40.53%, and 12.43%, respectively, over the M20 control mix, indicating accelerated early strength gain. However, all PET-modified mixes showed lower compressive strengths compared to the control mix at 21 and 28 days, with the reduction becoming more significant at higher PET concentrations. Notably, at 28 days, the mix with 4.2% PET showed a decrease in compressive strength of over 31.06% relative to the control mix. In contrast, split tensile strength increased consistently across all curing periods. The 4.0% PET mix achieved a 35.86% increase at 7 days, while the 3.8% PET mix showed the highest increase of 62.84% at 21 days. At 28 days, the 4.0% PET mix again showed the highest improvement, with a 45.35% increase in split tensile strength. These findings suggest that while a higher PET content may negatively impact long-term compressive strength, optimal PET incorporation can substantially enhance split tensile capacity, crack resistance, and ductility. Overall, the study demonstrates the sustainable utility of PET waste as a partial sand replacement in concrete, improving specific mechanical properties and promoting environmental sustainability. The results further confirm that compressive and tensile strengths tend to decrease with increasing PET content beyond optimal levels.